Handbook of fire and explosion protection engineering principles for oil, gas, chemical and related facilities - Nolan, Dennis P. (Elsevier Inc., 2011)
The security and economic stability of many nations and of multinational oil companies are highly dependent on the safe and uninterrupted operation of their oil, gas, and chemical facilities. One of the most critical impacts that can occur to these operations are fires and explosions from accidental or political incidents. This publication is intended as a general engineering handbook and reference guideline for those personnel involved with fire and explosion protection, and protection aspects of these critical facilities. The first edition of this book was published when there was not much information available on the process safety, the US CSB had not been established and the CCPS was just beginning to publish its guidance books on process safety. At that time there was a considerable void of process safety information that may have lead to some serious incidents that occurred in the industry. The main objective of the 2nd edition of this book is to update and expand the information to the current practices of process safety management and technical engineering improvements which have occurred since the original publication.
Keywords: Chemical plants -- Fires and fire prevention.; Petroleum refineries -- Fires and fire prevention.; Explosions.; Explosions -- Safety measures.; elektronické knihy; electronic books